1990
DOI: 10.21273/jashs.115.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Thinning of Spur `Delicious' Apples by Shade, Terbacil, Carbaryl, and Ethephon

Abstract: Terbacil applied to whole-spur `Delicious' apple (Malus domestica Borkh.) trees reduced photosynthesis and fruit set. The addition of the surfactant X-77 to terbacil sprays increased fruit thinning and leaf injury. Terbacil sprays applied to leaves only (fruit covered with foil) were as effective as when applied to leaves plus fruit. Dipping fruit alone in a terbacil solution did not cause abscission. Shading trees for 4 days with 92% polypropylene shade material reduced frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 8 publications
(6 reference statements)
0
24
1
Order By: Relevance
“…Through experiments involving defoliation treatments, these authors suggested that ethylene is the last hormonal effector of fruitlet abscission during this period. Actually, it is well known that exogenous ethylene or promoters induce fruit abscission in various fruit trees (Byers et al 1990a;Untiedt and Blanke 2001). Furthermore, reductions in the abscission rates during citrus fruit set have been obtained using ethylene biosynthesis inhibitors like 2-aminoethoxyvinyl glycine (AVG; see Ogata et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Through experiments involving defoliation treatments, these authors suggested that ethylene is the last hormonal effector of fruitlet abscission during this period. Actually, it is well known that exogenous ethylene or promoters induce fruit abscission in various fruit trees (Byers et al 1990a;Untiedt and Blanke 2001). Furthermore, reductions in the abscission rates during citrus fruit set have been obtained using ethylene biosynthesis inhibitors like 2-aminoethoxyvinyl glycine (AVG; see Ogata et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Partial defoliation of citrus seedlings, however, can increase photosynthetic rates of remaining leaves in proportion to the number of vegetative buds that are allowed to regrow (Syvertsen, 1994). Canopy shading or application of photosynthetic inhibitors shortly after bloom reduced carbohydrate available to developing fruitlets and increased early fruit abscission of orange (Moss, 1976), litchi (Yuan and Huang, 1988), peach (Byers et al, 1985), and apple trees (Byers et al, 1985(Byers et al, , 1990Yuan and Greene, 2000a). In addition, fruit weight from girdled branches at harvest decreased with decreasing leaf area per fruit in various fruit crops (Fishler et al, 1983;Roe et al, 1997;Yuan and Greene, 2000b).…”
mentioning
confidence: 99%
“…In the present study, temperatures on the day of application and for the following 3 d were >21 ºC except for 2001, when temperatures were 19 and 16 ºC the day of and the day after treatment (Table 1); that year ethephon signifi cantly reduced yield (Table 5). Byers et al (1990) showed that chemical thinners may be more active during periods of low light, but solar radiation was relatively high for all experiments in the present study except for 2002, when yield per tree, number of fruit harvested per tree and crop density were not affected by treatment. Thinning spur 'Deli-ciousʼ has been inconsistently affected by fruit size at the time of treatment.…”
Section: Discussionmentioning
confidence: 46%